Karakteristik Mutu Mikrobiologi (Total BAL, Yeast, Antibakteri) dan pH Masker Kefir Ekstrak Bunga Telang Selama Penyimpanan Suhu Rendah 4-6°C - Sabilah, Raisha Putri; Wulandari, Eka; Pratama, Andry (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the effect of storage time for kefir masks with butterfly pea flower extract on microbiological characteristics (total lactic acid bacteria, total yeast, and antibacterial activity) and pH at low temperatures (4-6?). The research was conducted using an experimental method using a Completely Randomized Design (CRD) with 4 treatments based on storage time (P1 = day 1, P2 = day 4, P3 = day 7, and P4 = day 10) and 5 repetitions. Data were analyzed using variance followed by an orthogonal polynomial test. The results of the study showed that storage time at low temperatures (4-6?) of kefir mask with the butterfly pea flower extract increased total LAB, total yeast, and antibacterial activity. However, it gave the same results for pH. On the 10th day of storage time with low temperatures (4-6?) of kefir mask with the butterfly pea flower extract produced a total LAB of 5.02 x 107 cfu/mL, total yeast of 4.47 x 107 cfu/mL, antibacterial activity of 6,4 mm, and pH of 4.28.